Antihyperuricemic Activity of Peperomia pellucida (L.) Kunth Ethanol Extract and Its Effects on Relative Kidney Weight in Rats - Rahmawati, Riska Dewi; Hariyatmi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effectiveness of ethanolic extract of Peperomia pellucida in reducing blood uric acid levels while assessing its subchronic effects on relative kidney weight. An in vivo experiment was conducted using 24 male white rats (Rattus norvegicus), which were randomly allocated into six treatment groups (4 rats per group): a normal control (P0), a negative control receiving 0.1% Na-CMC (P1), a positive control receiving allopurinol at 1.8 mg/200 g body weight (BW) (P2), and three groups receiving P. pellucida extract at doses of 100 mg/kg BW (P3), 150 mg/kg BW (P4), and 200 mg/kg BW (P5). Hyperuricemia was induced by intraperitoneal administration of potassium oxonate at 250 mg/kg BW. Treatments were administered daily for 28 days, followed by measurement of final blood uric acid levels using Point-of-Care Testing and determination of the relative kidney organ index. Welch’s ANOVA showed a significant effect of extract administration on the reduction in blood uric acid levels (F(5, 7.739) = 14.630; p = 0.001). ANCOVA further confirmed significant differences in treatment effectiveness among the groups (F(5, 17) = 3.897; p = 0.015). The 200 mg/kg BW dose (P5) produced the greatest reduction in uric acid levels, reaching 46.06 ± 10.80%, and was statistically comparable to the positive allopurinol control (50.95 ± 13.19%; p > 0.05). In contrast, the Kruskal–Wallis test showed no significant differences in the relative kidney organ index among groups (H(5) = 4.262; p = 0.512), with mean values ranging from 0.82 ± 0.06% to 0.96 ± 0.54%. These findings indicate that P. pellucida extract at 200 mg/kg BW effectively reduces blood uric acid levels without causing significant changes in relative kidney weight during 28 days of administration.